The Effect of Flipped Classroom On Critical Thinking Disposition in Nursing Students - Shadi Dehghanzadeh; Fateme Jafaraghaie; Hamid Khordadi Astane (مجله ایرانی آموزش در علوم پزشکی, 2018)
Introduction: Critical thinking is an ongoing debate in medical education, and application of modern educational methods such as flipped classroom have been suggested for developing this concept. The purpose of this study was to investigate the effect of flipped classroom on nursing students’ critical thinking disposition. Methods: This quasi-experimental one-group pre- and post-test study was conducted in 2016 on 43 nursing students of Azad University, Rasht Branch who had musculoskeletal disorders course. Subjects were selected by census method. Before each session, students observed the electronic contents, including recorded lectures and studied some parts of the textbook while the class time was used for cooperation in small groups to discuss the questions and clinical scenarios. Critical thinking disposition was assessed before and after the implementation of flipped classroom method using Ricketts’ Critical Thinking Disposition Questionnaire. The data were analyzed by means of one-sample t-test, paired t-test, Pearson correlation coefficient, and ANOVA. Results: The mean and the standard deviation of the critical thinking disposition scores before and after the intervention were 103.63±13.26 and 122.53±10.57 (total score=165) respectively. Total critical thinking disposition and the domain of intellectual engagement showed a significant increase after the intervention (p=0. 0001). Conclusion: The results showed that the flipped classroom method had a positive effect on critical thinking disposition of the nursing students. Investigation of students’ satisfaction with learning with this method as a factor in fostering critical thinking is suggested for future research.